2019
DOI: 10.1111/jcpe.13188
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of single molecular biomarkers in gingival crevicular fluid for the diagnosis of periodontitis: A systematic review and meta‐analysis

Abstract: Aim To analyse, by means of a meta‐analytical approach, the diagnostic accuracy of molecular biomarkers in gingival crevicular fluid (GCF) for the detection of periodontitis in systemically healthy subjects. Material and Methods Studies on GCF molecular biomarkers providing a binary classification table (or sensitivity and specificity values and group sample sizes) in individuals with clinically diagnosed periodontitis were considered eligible. The search was performed using six electronic databases. The metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
65
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(70 citation statements)
references
References 58 publications
(116 reference statements)
5
65
0
Order By: Relevance
“…Firstly, aMMP-8 levels in mouthrinse were significantly lower among healthy patients compared with patients in more severe periodontitis stages and grades (Kruskal-Wallis test, p < 0.01; Figure 1), as would be expected from an effective diagnostic tool to classify periodontal health and disease [14][15][16][17][18][19][20][21][22][23][24][25][26]. This result is also in agreement with previous studies that have shown that aMMP-8 predicts very well future periodontal breakdown (positive predictive values range between 81.8%-94.7%) [35]. Secondly, BOP and VPI levels were also associated with the periodontitis stage and grade (Kruskal-Wallis test, p < 0.01); Figure 1), but these two parameters were also moderately correlated with each other (Spearman's rho = 0.586, p < 0.001).…”
Section: Main Textsupporting
confidence: 90%
See 3 more Smart Citations
“…Firstly, aMMP-8 levels in mouthrinse were significantly lower among healthy patients compared with patients in more severe periodontitis stages and grades (Kruskal-Wallis test, p < 0.01; Figure 1), as would be expected from an effective diagnostic tool to classify periodontal health and disease [14][15][16][17][18][19][20][21][22][23][24][25][26]. This result is also in agreement with previous studies that have shown that aMMP-8 predicts very well future periodontal breakdown (positive predictive values range between 81.8%-94.7%) [35]. Secondly, BOP and VPI levels were also associated with the periodontitis stage and grade (Kruskal-Wallis test, p < 0.01); Figure 1), but these two parameters were also moderately correlated with each other (Spearman's rho = 0.586, p < 0.001).…”
Section: Main Textsupporting
confidence: 90%
“…Many other potential biomarkers to detect periodontitis and related systemic diseases have been investigated as well [35][36][37][38][39][40][41][42][43]; these include, along with others, asymmetric dimethylarginine (ADMA), C-reactive protein, interferon gamma (IFN-γ), interleukin-6 (IL-6), macrophage inflammatory protein-1α (MIP-1α), PMN elastase, vitamin C and also antioxidants [35][36][37][38][39][40][41][42][43]. For example, vitamin C is linked to oxidative MMP-activation cascade by its recorded ability to prevent the oxidative activation of proMMP-8 [44].…”
Section: Main Textmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, metabolic profiling of saliva (combination of cadaverine, 5-oxoproline, and histidine) identified individuals, according to the CDC/AAP definition, with moderate/severe periodontitis with an AUC of 0.88 [40]. Moreover, a meta-analysis was recently performed for four biomarkers in GCF: MMP-8, elastase, cathepsin, and trypsin [41]. The median sensitivity and specificity were 77% and 92% for MMP-8, 75% and 81% for elastase, 73% and 67% for cathepsin, and 71% and 66% for trypsin, respectively.…”
Section: Discussionmentioning
confidence: 99%